Functional implication of synaptophysin upregulation with traumatic brain injury adult rats. Issue 1 (28th March 2016) - Liu, Jun; Dan, Qi‐Qin; Zhao, Nan; Li, Jun‐Yan; Li, Jin; Chang, Qian; Su, Ping; Cen, Jiang‐Chang
Abstract : Objective: This study aimed to investigate the neurobehavioral change in rats subjected traumatic brain injury (TBI) and explore the mechanism involving in the expression of synaptophysin. Methods: Sprague Dawley rats were randomly divided into Sham and TBI groups. TBI was induced by modified Feeney's freefall method. Neurological severity score (NSS) was assessed at 2 days, 4 days and 7 days after operation, and cortex was obtained at 7 days post TBI. Then, Quantitative real‐time polymerase chain reaction and western blot were used to detect the mRNA and protein expression of synaptophysin. Lastly, immunofluorescence staining was conducted to localize synaptophysin. Results: NSS was significantly aggregated after TBI, compared with the Sham group. The mRNA and protein expressions of synaptophysin were increased in TBI group than that in the Sham group. Synaptophysin‐positive cells were also enhanced in TBI group and mainly expressed in neutrophil. Conclusion: The nerve function change induced by TBI was associated with the upregulation of synaptophysin expression.